Pengaruh Self-Efficacy dan Lingkungan Teman Sebaya Terhadap Motivasi Belajar dan Implikasinya Terhadap Hasil Belajar - Fajar Nur’alim; Ati Sadiah; Ai Nur Solihat (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to determine the influence of self-efficacy and the peer environment on learning motivation and its implications for learning outcomes in Grade X at State Senior High School 6 Tasikmalaya. This study employs a quantitative research method, with a sampling technique using probability sampling through simple random sampling, involving a total of 209 participants. The results of the path analysis indicate a significant influence of self-efficacy on learning motivation, a significant significant influence between peer environment and learning motivation, there is a significant influence between self-efficacy and learning outcomes, there is a significant influence between peer environment and learning outcomes, there is a significant influence between learning motivation and learning outcomes, there is a significant influence between self-efficacy and learning outcomes through learning motivation, there is a significant influence between peer on learning outcomes through learning motivation.